Incidence of sensitization to specific inhalatory allergens in patients suffering from allergic rhinitis - Buljčik Čupić, Maja; Savović, Slobodan; Hromiš, Sanja; Lemajić Komazec, Slobodanka; Karaba Jakovljević, Dea (Vojnosanitetski pregled, 2021)
Abstract Backgound/Aim. Allergic rhinitis is the most frequent type of rhinitis affecting more than 600 million people worldwide. As incidence increases, it is important to know about the characteristics, the allergens that exacerbate it as well as effects of allergic rhinitis on population. The aim of this study was to determine among patients with chronic rhinitis the number of patients positive to standard inhaled allergens, their distribution by sex, age and to determine the type and frequency of allergic sensitization to specific inhalatory allergens. Methods. Data was collected from 514 patients tested for standard inhalatory allergens via the skin prick test from 01.01.2016 to 31.12. 2016. Age, sex and concomitant diseases as well an analysis of type and frequency of hypersensitivity to different allergens were assessed and recorded. Results. Of 514 patients, 307 patients, with an average age of 29.6 ± 8.88 years had a positive skin prick test. The sex ratio was 1.2 : 1 in favor of the females. Outdoor allergens affected 81.2% of all patients while indoor allergens 66.4% of them. Weed pollen (71%), grass pollen (61%) and Dermatophagoides pteronyssinus (46%) were the most common allergens. Most patients were sensitized to 1 (22%) or 2 (22%) allergens, while 20% of patients were simultaneously sensitized to 3 allergens. Conclusion. Most patients with the symptoms of chronic rhinitis had a positive allergic reaction. Those in their third decade of life were the most commonly affected. Outdoor allergens were the most prevalent allergen group, and weed pollen was the most frequent type of allergen.